Fitness of Malaysian imidazolinone-resistant weedy rice and their growth responses to various herbicides - Mohammad Azizi Hj. Jamil; Muhammad Saiful Ahmad Hamdani; Zulkarami Berahim; Nik Amelia Nik Mustapha; Mahmudul Hasan; Dilipkumar Masilamany (Penerbit Universiti Kebangsaan Malaysia, 2025)
The Ser-653-Asn mutation has been identified as the primary factor responsible for imidazolinone (IMI)-resistant weedy rice in Malaysia. This has led to inquiries regarding whether this specific mutation might impose a fitness penalty on the weedy rice population. Consequently, this research examines the fitness of IMI-resistant weedy rice and evaluates its growth responses to different herbicide modes of action (MOA). In the first experiment, the IMI-resistant weedy rice, susceptible weedy rice, and IMI-rice were germinated. Subsequently, the weedy rice seedlings were transplanted interspersed with IMI-rice at varying planting densities. The populations were categorised into herbicide-treated and untreated groups. Photosynthesis parameters were measured at 30, 45, 60, and 75 days after sowing (DAS). Morphological parameters such as leaf area, plant height, dry weight, and tiller numbers were collected after 80 DAS. In the second experiment, the IMI resistant weedy rice was subjected to different herbicide modes of action (MOA) to evaluate their growth responses. The study was carried out in two parts: Pre-emergence and post-emergence pot trial. In pre-emergence pot trial, the study was conducted using pre-germinated seeds in petri dishes and treated with pretilachlor at 1, 3 and 5 DAS. For post-emergence pot trial, pre-germinated seeds were planted in trays, and at 1-2 leaf stage were treated with quinclorac, imazethapyr and clethodim at the recommended rate. The germination rate and plant height were measured in pre-emergence pot trials after 14 DAS, while survivability and dry weight were recorded in post-emergence pot trials after 21 DAS. A slight fitness cost was observed in IMI-resistant weedy rice, in which it has larger leaf areas and shorter plant height compared to IMI-susceptible weedy rice and MR220CL2 rice. There were no significant differences between the populations in the other morphological parameters observed. In the growth response study, IMI-resistant weedy rice has been observed to have different responses to different herbicide’s MOA. Pretilachlor was effective when applied at 1 DAS, and its efficacy reducing when applied later. Clethodim was effective in controlling IMI-resistant weedy rice, quinclorac was ineffective and imazethapyr was only effective in controlling IMI-susceptible weedy rice. Further studies are necessary to establish a standardised assessment of fitness costs and to employ and integrate other MOAs in the management of weedy rice.